The Impact of the Group Maturity on the Software Development Team Effectiveness: An Experience Report - Cadette, William De Araujo; Felizardo, Fernando; Zavadski, Arthur Cattaneo; Leal, Gislaine Camila Lapasini; Balancieri, Renato; Colanzi, Thelma Elita (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2022)
Project-Based Learning (PBL) is an active learning method in which students gain knowledge and skills by exploring real-world problems for an extended period of time. Existing studies point out that soft skills related to working in groups, such as communication skills, teamwork skills, and problem-solving skills, can be enhanced through PBL. Aspects of the group are fundamental to the success of any software project. In this context, this work seeks to investigate the group’s maturity and its relationship with the effectiveness of Agile Software Development teams in PBL. To do so, we conduct a study in the context of a discipline of the Software Engineering graduate course in which PBL is adopted. At the end of the semester, a questionnaire was applied to eight teams of graduating students, involving a total of 29 students, to measure aspects of the group’s maturity, later these aspects were correlated with the effectiveness of the teams. The obtained results point out that group maturity and team effectiveness are directly correlated. The results also show three aspects of group maturity that, if improved, will possibly improve the effectiveness of teams in software development: mutual trust, backup behavior and cohesiveness. Furthermore, from this experience we were able to derive some assumptions and directions for supporting instructors to stimulate the improvement of the soft skills relevant to both team effectiveness and software industry when applying PLB in their classes.